FRI0660 Impact of ultrasound in treatment decision of rheumatoid arthritis. (15th June 2017) - Gutierrez, M; Pineda, C; Espinosa, R; Hernandez, C; Ventura, L; Lozada, C; Silveira, LH; Rodriguez, G; Cruz, E; Vargas, A; Bertolazzi, C; Lozada, AC
Abstract : Background: Ultrasound (US) is an important tool to support the clinician in the diagnosis and treatment monitoring of rheumatoid arthritis (RA). The EULAR recommended it for the follow up of RA patients. In spite of the evidence supporting the value of US, the real impact in treatment decisions is not clearly defined. Objectives: To investigate the impact of US findings in the treatment decisions of rheumatologists in patients with RA in a real-life setting. Additionally, to verify the US findings that play a role in change of treatment, types of changes and their distribution. Methods: RA patients were included. As a first step, the rheumatologist performed a clinical examination (including DAS28) and recorded the treatment approach suggested according his clinical evaluation (i.e. starting, changing or stopping pharmacological medication as well as local injection). In the same day, after the clinical assessment, the patients were sent for an US examination using the 7-joint score, which was performed by an independent rheumatologist sonographer who reported the US findings to the same rheumatologist that previously evaluated clinically the patient. This last decided, according to the US findings to maintain or change the previous suggested therapy. Additionally, the clinical rheumatologist reported the reasons which induced to change or not the treatment after the US examination Results: A total of 128 RA patients were included [female 117 (91.4%), male 11 (8.59%)], with mean ± SD disease duration of 9.88±8.22 years. Ninety-four patients (73.4%) had active disease according the DAS 28, whereas 34 (26.5%) were considered in remission. US findings influenced a change in the treatment in 56 cases (43.7%) (47 with clinical active disease and 9 in remission). Among the main reasons that induced a change in the treatment based on the US examinations were: grade of synovitis (25%), higher number of synovitis than clinical examination (16.6%) and presence of power Doppler (PD) (16.7%). The most frequent treatment changes were increasing dose or start a new combination of DMARDs [39 patients (69.5%)]. The multiple logistic regression analysis showed that synovitis of 2nd metacarpophalangeal joint (MCPj) was the US finding with more influence in the decision to change treatment (p=0.016). With respect to distribution, 122 patients (95.3%) had al least one joint with US synovitis and 76 patients (59.3%) had at least one joint with PD. The wrist, 2nd MCPj and 2nd metatarsophalangeal joint (MTPj) were the most affected in terms of synovitis whereas the 5th MTPj showed more erosions (37.7%) and the extensor fingers tendons showed more tenosynovitis (23.02%). Conclusions: US demonstrated to play an important role in the treatment decision of RA patients. The impact was more frequent in patients with active disease but also affected the decision in patients considered in clinical remission. Disclosure of Interest: None declared